Răspuns :
(2x²+y) = (2x²)² + 2·2x·y + y² = [tex] 2x^{4} [/tex] + 4xy + y²
(2x²-y) = (2x²)² - 2·2x·y + y² = [tex] 2x^{4} [/tex] - 4xy + y²
(x+y)(x-y) = x² - y²
[tex] 2x^{4} [/tex] + 4xy + y² - ([tex] 2x^{4} [/tex] - 4xy + y²) + x² - y² =
= [tex] 2x^{4} [/tex] + 4xy + y² - [tex] 2x^{4} [/tex] + 4xy - y² + x² - y² =
= 4xy + 4xy + x² - y² =
= 8xy + x² -y²
(2x²-y) = (2x²)² - 2·2x·y + y² = [tex] 2x^{4} [/tex] - 4xy + y²
(x+y)(x-y) = x² - y²
[tex] 2x^{4} [/tex] + 4xy + y² - ([tex] 2x^{4} [/tex] - 4xy + y²) + x² - y² =
= [tex] 2x^{4} [/tex] + 4xy + y² - [tex] 2x^{4} [/tex] + 4xy - y² + x² - y² =
= 4xy + 4xy + x² - y² =
= 8xy + x² -y²